Javid Nama and Zindagi: A Comparative Analysis - Azmat Hayat (بازیافت)
In this article Javid Nama, The famous masnavi of Allama Muhammad Iqbal and Zindgi, a novel penned down by renowned author Ch. Afzal Haq has been compared critically. Interesting resemblances between both the books are explored in this comparative study. This study probes that Javid Nama and Zindgi not only resemble regarding subject matter and thought but also in the realm of time and space. For example the time of publication, place of publication, social and intellectual context of both book are same. Both the books despite generic differences have the same novelistic, dramatic and imaginative elements.